Directors : from stage to screen and back again - Lehman, Susan Beth (Intellect, 2013)
The interviews contained in Directors: From Stage to Screen and Back Again demonstrate the myriad ways in which a theater background can engender innovative and stimulating work in film. As unique and idiosyncratic as the personalities they feature, the Director's conversations with Susan Beth Lehman range over a vast field of topics. Each one traces its subject's personal artistic journey and explores how he or she handled the lessons and challenges of moving from stage to screen.